Orality in the cultural area of Bosnia and Herzegovina - Ćurguz Jelena (CM. Communication and Media)
Starting off from Ong's theory of orality and literacy (Ong, 1982/2012), the aim of this paper is to show that in social communication in the cultural area of Bosnia and Herzegovina, oral communication has been significantly preserved with the features of the primary orality, which is often ritualistic (Carey, 2009) and high-context (Hall, 1981). The study demonstrates that there are numerous traces of the primary orality in the celebration of family and religious holidays (such as Slava), as well as various folk customs (local celebrations, feasts and fairs, folk competitions, masquerades, carolers, weddings and funerals), and in everyday socializing (e.g. in cafes and among neighbors). Most customs are permeated with verbal and non-verbal ritual communication - established greetings and congratulations, toasts, jokes, songs, dances, processions, shared meals, gift-giving and decorations, and sometimes piercing sounds. Also, the old oral literature and expressions are still alive today, which are passed down from generation to generation - e.g. songs, fairy tales, proverbs, sayings, anecdotes, curses, rhymes and lullabies, and many people have specific nicknames. Cultivating orality is one of the ways of preserving heritage, maintaining close interpersonal relationships and strengthening ties in the community, which is especially important today, when human communication is increasingly mediated by different technologies, which can lead to loneliness.